Classification of helicopters for passive radar - theoretical studies and measurements - Qiao, Na (2017)
This paper focus on the classification of helicopters for passive bistatic radar. The model of rotating blades has been established based on the mechanism of rotation. We build up a hardware system for stimulating helicopter rotator blades, provide it appropriate voltage to let it rotate in almost constant speed. From the previous research, author get the time-frequency domain figure based on theory and formula. In our experiment, we test in different speed, length, and number of blades result different group of data. Using MatLab figure out these data get from vector network analyzer (VNA) into time-frequency micro-Doppler image to verify whether the previous theory method can establish. Instead of testing using stimulating blades, we testing an air fan in the north spine campus to see if interference exist whether will affect our result.